Características morfofisiológicas e produtividade de cana-de-açúcar variam de acordo com a cultivar e o regime hídrico - De Silva, Marcelo Almeida [UNESP]; Arantes, Marcel Tomás [UNESP]; De Rhein, Andressa Freitas Lima [UNESP]; Pincelli, Renata Passos [UNESP]; Dos Santos, Claudiana Moura [UNESP]; Moura, Paula Caroline Silva [UNESP] (My University, 2015)
Studies on morphological and physiological variables are important to assist in the characterization and understanding of the stress tolerance mechanisms and the choice of cultivars with better performance in contrasting environments, such as, the irrigated and rainfed ones. The study aimed at differentiating cultivars of sugar cane in irrigated and rainfed environments through morphological and physiological variables, and their responses concerning productivity. The experiment was carried out in Jaú-SP using the RB867515 and RB855536 cultivars. The morphological variables were as follows: length of stems, number of tillers, specific leaf mass (SLM) and leaf area index (LAI), and physiological variables: photochemical efficiency of photosystem II (Fv/Fm), stomatal conductance (gs), relative water content (RWC), SPAD index and chlorophyll content (CC a+b). The evaluations were performed at 60, 120, 180, 240 days after cutting (DAC) in the third cycle, and at the last evaluation, stem (TCH) and sugar (TPH) yield were obtained. The results showed that the RB855536 cultivar has higher values of morphological variables, i.e., length of stems and number of tiller, and of physiological variables, i. e., stomatal conductance and chlorophyll content. Also, it had higher sugar yield under appropriate water regime during the development cycle. The RB867515 cultivar produced more stems and sugar under the rainfed water regime, and higher values of morphological variables such as number of tillers and specific leaf mass, and of physiological variables such as chlorophyll fluorescence (Fv/Fm), stomatal conductance, chlorophyll content and relative water content in the leaf.
Morphophysiological traits and yield of sugar cane vary according to the cultivar and water regime
Keywords: Cultivars; Irrigation; Saccharum spp; Water stress; Yield